2011
DOI: 10.1021/jo201630e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Aminoalkylation of Arenes, Heteroarenes, and Alkenes via Ni-Catalyzed Negishi Cross-Coupling Reactions

Abstract: A room-temperature Ni-catalyzed cross-coupling of aryl, heteroaryl, and alkenyl electrophiles with aminoalkylzinc bromides, readily available from the corresponding aminoalkyl chlorides via Grignard reagents, was developed. The reaction allows a convenient one-step preparation of various aminoalkyl products, including piperidine and tropane derivatives. Such functionalized amine moieties are widely present in various biologically active molecules. Aryl, heteroaryl, and alkenyl iodides, bromides, chlorides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Knochel et al have reported the single example of reduction of a 2‐substituted quinoline 6 to the corresponding 2‐substituted 1,2,3,4‐tetrahydroquinoline scaffold 7 applied to the synthesis of the Hancock alkaloids not reliant upon hydrogenation or transfer hydrogenation. In their synthesis, reaction of quinaldine 14 with paraformaldehyde gave 52 in 72 % yield (based on returned starting material), and reduction of 52 was accomplished using NaBH 4 and NiCl 2 in MeOH, delivering 2‐substituted 1,2,3,4‐tetrahydroquinoline 53 in 87 % yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knochel et al have reported the single example of reduction of a 2‐substituted quinoline 6 to the corresponding 2‐substituted 1,2,3,4‐tetrahydroquinoline scaffold 7 applied to the synthesis of the Hancock alkaloids not reliant upon hydrogenation or transfer hydrogenation. In their synthesis, reaction of quinaldine 14 with paraformaldehyde gave 52 in 72 % yield (based on returned starting material), and reduction of 52 was accomplished using NaBH 4 and NiCl 2 in MeOH, delivering 2‐substituted 1,2,3,4‐tetrahydroquinoline 53 in 87 % yield.…”
Section: Discussionmentioning
confidence: 99%
“…The low yield of this process was due to the competitive formation of 191 and 192 , the result of ring‐opening of the intermediate carbanion as the major pathway to give the corresponding metallated amide anion as the driving force, which is then either trapped upon work‐up to give 191 , or reacts with BuBr to give 192 (Scheme ). Although this is a relatively inefficient method for the preparation of (±)‐angustureine 1 , it is instructive to compare it to the approach of Knochel et al (Scheme ) which involves the Turbo Grignard reagent 55 (i.e., a homologated form of the carbanion derived from 190 , the homologue 55 not being susceptible to ring‐opening in the same way).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This strategy renders reductive elimination faster than β‐hydride elimination, thereby affording the desired products 3g. Recently, seminal work by the groups of Lipshutz,3l Organ,3g Knochel,3c,e Biscoe,3b and Buchwald3f have further shown that these sterically hindered ligands also enable the efficient cross‐coupling of alkylzinc reagents with heteroaryl halides using palladium and nickel catalysts to generate alkylated heteroarenes. Despite having this strategy already at our disposal, the availability of a simple reaction protocol which allows us to conduct similar transformations in the absence of custom‐designed ligands would no doubt have a significant impact on the cost‐effective and sustainable syntheses of pharmaceuticals and drug candidates.…”
Section: Methodsmentioning
confidence: 99%
“…[11] However,since palladium [12] and nickel, [13] the favored transition metal catalysts for couplings,a re expensive [14] and/or toxic, [15] we envisioned the performance of cross-couplings with organozinc pivalates using industrial friendly transition metal catalysts.Cobalt-catalyzed couplings are of special interest since cobalt salts are much less toxic than palladium salts [15] and additionally are ca. [11] However,since palladium [12] and nickel, [13] the favored transition metal catalysts for couplings,a re expensive [14] and/or toxic, [15] we envisioned the performance of cross-couplings with organozinc pivalates using industrial friendly transition metal catalysts.Cobalt-catalyzed couplings are of special interest since cobalt salts are much less toxic than palladium salts [15] and additionally are ca.…”
mentioning
confidence: 99%